Ocular Vestibular-Evoked Myogenic Potential Amplitudes Elicited at 4 kHz Optimize Detection of Superior Semicircular Canal Dehiscence - Tran, Emma D.; Swanson, Austin; Sharon, Jeffrey D.; Vaisbuch, Yona; Blevins, Nikolas H.; Fitzgerald, Matthew B.; Steenerson, Kristen K. (Frontiers in Neurology, 2020)
Introduction: High-resolution temporal bone computed tomography (CT) is considered the gold standard for diagnosing superior semicircular canal dehiscence (SCD). However, CT has been shown over-detect SCD and provide results that may not align with patient-reported symptoms. Ocular vestibular-evoked myogenic potentials (oVEMPs)—most commonly conducted at 500 Hz stimulation—are increasingly used to support the diagnosis and management of SCD. Previous research reported that stimulation at higher frequencies such as 4 kHz can have near-perfect sensitivity and specificity in detecting radiographic SCD. With a larger cohort, we seek to understand the sensitivity and specificity of 4 kHz oVEMPs for detecting clinically significant SCD, as well as subgroups of radiographic, symptomatic, and surgical SCD. We also investigate whether assessing the 4 kHz oVEMP n10-p15 amplitude rather than the binary n10 response alone would optimize the detection of SCD. Methods: We conducted a cross-sectional study of patients who have undergone oVEMP testing at 4 kHz. Using the diagnostic criteria proposed by Ward et al., patients were determined to have SCD if dehiscence was confirmed on temporal bone CT by two reviewers, patient-reported characteristic symptoms, and if they had at least one positive vestibular or audiometric test suggestive of SCD. Receiver operating characteristic (ROC) analysis was conducted to identify the optimal 4 kHz oVEMP amplitude cut-off. Comparison of 4 kHz oVEMP amplitude across radiographic, symptomatic, and surgical SCD subgroups was conducted using the Mann-Whitney U test. Results: Nine hundred two patients (n, ears = 1,804) underwent 4 kHz oVEMP testing. After evaluating 150 temporal bone CTs, we identified 49 patients (n, ears = 61) who had radiographic SCD. Of those, 33 patients (n, ears = 37) were determined to have clinically significant SCD. For this study cohort, 4 kHz oVEMP responses had a sensitivity of 86.5% and a specificity of 87.8%. ROC analysis demonstrated that accounting for the inter-amplitude of 4 kHz oVEMP was more accurate in detecting SCD than the presence of n10 response alone (AUC 91 vs. 87%). Additionally, using an amplitude cut-off of 15uV reduces false positive results and improves specificity to 96.8%. Assessing 4 kHz oVEMP response across SCD subgroups demonstrated that surgical and symptomatic SCD cases had significantly higher amplitudes, while radiographic SCD cases without characteristic symptoms had similar amplitudes compared to cases without evidence of SCD. Conclusion: Our results suggest that accounting for 4 kHz oVEMP amplitude can improve detection of SCD compared to the binary presence of n10 response. The 4 kHz oVEMP amplitude cut-off that maximizes sensitivity and specificity for our cohort is 15 uV. Our results also suggest that 4 kHz oVEMP amplitudes align better with symptomatic SCD cases compared to cases in which there is radiographic SCD but no characteristic symptoms.